The effectiveness of photodynamic therapy on planktonic cells and biofilms and its role in wound healing. (September 2014) - Percival, Steven L; Suleman, Louise; Francolini, Iolanda; Donelli, Gianfranco
ABSTRACT : Photodynamic therapy (PDT) is the application of a photoactive dye followed by irradiation that leads to the death of microbial cells in the presence of oxygen. Its use for controlling biofilms has been documented in many areas, particularly oral care. However, the potential use of PDT in the treatment of chronic wound-associated microbial biofilms has sparked much interest in the field of wound care. The aim of this article is to provide an overview on the effectiveness of PDT on in vitro and in vivo biofilms, their potential application in both the prevention and management of wound biofilm infections and their prospective role in the enhancement of wound healing.